5.20.36 Problems 3501 to 3600

Table 5.977: Second or higher order ODE with constant coefficients

#

ODE

Mathematica

Maple

18102

\[ {}2 y^{\prime \prime \prime }+y^{\prime \prime }-5 y^{\prime }+2 y = 0 \]

18189

\[ {}y^{\prime \prime }-k y = 0 \]

18251

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 4 x \]

18253

\[ {}y^{\prime \prime }-2 y^{\prime } = 6 \]

18254

\[ {}y^{\prime \prime }-2 y = \sin \left (x \right ) \]

18255

\[ {}y^{\prime \prime } = {\mathrm e}^{x} \]

18256

\[ {}y^{\prime \prime }-2 y^{\prime } = 4 \]

18257

\[ {}y^{\prime \prime }-y = \sin \left (x \right ) \]

18259

\[ {}y^{\prime \prime }+2 y^{\prime } = 6 \,{\mathrm e}^{x} \]

18262

\[ {}y^{\prime \prime }-y = 0 \]

18264

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

18265

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

18267

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

18268

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 0 \]

18269

\[ {}y^{\prime \prime }+y^{\prime } = 0 \]

18272

\[ {}y^{\prime \prime }+y = 0 \]

18273

\[ {}y^{\prime \prime }-y = 0 \]

18288

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

18289

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

18290

\[ {}y^{\prime \prime }+8 y = 0 \]

18291

\[ {}2 y^{\prime \prime }-4 y^{\prime }+8 y = 0 \]

18292

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

18293

\[ {}y^{\prime \prime }-9 y^{\prime }+20 y = 0 \]

18294

\[ {}2 y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

18295

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

18296

\[ {}y^{\prime \prime }+y^{\prime } = 0 \]

18297

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 0 \]

18298

\[ {}4 y^{\prime \prime }+20 y^{\prime }+25 y = 0 \]

18299

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

18300

\[ {}y^{\prime \prime } = 4 y \]

18301

\[ {}4 y^{\prime \prime }-8 y^{\prime }+7 y = 0 \]

18302

\[ {}2 y^{\prime \prime }+y^{\prime }-y = 0 \]

18303

\[ {}16 y^{\prime \prime }-8 y^{\prime }+y = 0 \]

18304

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

18305

\[ {}y^{\prime \prime }+4 y^{\prime }-5 y = 0 \]

18306

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

18307

\[ {}y^{\prime \prime }-6 y^{\prime }+5 y = 0 \]

18308

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

18309

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

18310

\[ {}y^{\prime \prime }+4 y^{\prime }+2 y = 0 \]

18311

\[ {}y^{\prime \prime }+8 y^{\prime }-9 y = 0 \]

18323

\[ {}y^{\prime \prime }+3 y^{\prime }-10 y = 6 \,{\mathrm e}^{4 x} \]

18324

\[ {}y^{\prime \prime }+4 y = 3 \sin \left (x \right ) \]

18325

\[ {}y^{\prime \prime }+10 y^{\prime }+25 y = 14 \,{\mathrm e}^{-5 x} \]

18326

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 25 x^{2}+12 \]

18327

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 20 \,{\mathrm e}^{-2 x} \]

18328

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 14 \sin \left (2 x \right )-18 \cos \left (2 x \right ) \]

18329

\[ {}y^{\prime \prime }+y = 2 \cos \left (x \right ) \]

18330

\[ {}y^{\prime \prime }-2 y^{\prime } = 12 x -10 \]

18331

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 6 \,{\mathrm e}^{x} \]

18332

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = {\mathrm e}^{x} \sin \left (x \right ) \]

18333

\[ {}y^{\prime \prime }+y^{\prime } = 10 x^{4}+2 \]

18334

\[ {}y^{\prime \prime }+k^{2} y = \sin \left (b x \right ) \]

18335

\[ {}y^{\prime \prime }+4 y = 4 \cos \left (2 x \right )+6 \cos \left (x \right )+8 x^{2}-4 x \]

18336

\[ {}y^{\prime \prime }+9 y = 2 \sin \left (3 x \right )+4 \sin \left (x \right )-26 \,{\mathrm e}^{-2 x}+27 x^{3} \]

18337

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 2 x \]

18338

\[ {}y^{\prime \prime }-y^{\prime }-6 y = {\mathrm e}^{-x} \]

18339

\[ {}y^{\prime \prime }+4 y = \tan \left (2 x \right ) \]

18340

\[ {}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-x} \ln \left (x \right ) \]

18341

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 64 x \,{\mathrm e}^{-x} \]

18342

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = {\mathrm e}^{-x} \sec \left (2 x \right ) \]

18343

\[ {}2 y^{\prime \prime }+3 y^{\prime }+y = {\mathrm e}^{-3 x} \]

18344

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \frac {1}{1+{\mathrm e}^{-x}} \]

18345

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

18346

\[ {}y^{\prime \prime }+y = \cot \left (x \right )^{2} \]

18347

\[ {}y^{\prime \prime }+y = \cot \left (2 x \right ) \]

18348

\[ {}y^{\prime \prime }+y = x \cos \left (x \right ) \]

18349

\[ {}y^{\prime \prime }+y = \tan \left (x \right ) \]

18350

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \tan \left (x \right ) \]

18351

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \csc \left (x \right ) \]

18357

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+2 y^{\prime } = 0 \]

18358

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y^{\prime }-2 y = 0 \]

18359

\[ {}y^{\prime \prime \prime }-y = 0 \]

18360

\[ {}y^{\prime \prime \prime }+y = 0 \]

18361

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }+3 y^{\prime }+y = 0 \]

18362

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+6 y^{\prime \prime }+4 y^{\prime }+y = 0 \]

18363

\[ {}y^{\prime \prime \prime \prime }-y = 0 \]

18364

\[ {}y^{\prime \prime \prime \prime }+5 y^{\prime \prime }+4 y = 0 \]

18365

\[ {}y^{\prime \prime \prime \prime }+2 a^{2} y^{\prime \prime }+a^{4} y = 0 \]

18366

\[ {}y^{\prime \prime \prime \prime }+2 a^{2} y^{\prime \prime }+a^{4} y = 0 \]

18367

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+2 y^{\prime \prime }+2 y^{\prime }+y = 0 \]

18368

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-2 y^{\prime \prime }-6 y^{\prime }+5 y = 0 \]

18369

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = 0 \]

18370

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }-3 y^{\prime \prime }-5 y^{\prime }-2 y = 0 \]

18371

\[ {}y^{\left (5\right )}-6 y^{\prime \prime \prime \prime }-8 y^{\prime \prime \prime }+48 y^{\prime \prime }+16 y^{\prime }-96 y = 0 \]

18372

\[ {}y^{\prime \prime \prime \prime } = 0 \]

18373

\[ {}y^{\prime \prime \prime \prime } = \sin \left (x \right )+24 \]

18374

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+2 y^{\prime } = 10+42 \,{\mathrm e}^{3 x} \]

18375

\[ {}y^{\prime \prime \prime }-y^{\prime } = 1 \]

18380

\[ {}y^{\prime \prime }-4 y = {\mathrm e}^{2 x} \]

18381

\[ {}y^{\prime \prime }-y = x^{2} {\mathrm e}^{2 x} \]

18382

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 10 x^{3} {\mathrm e}^{-2 x} \]

18383

\[ {}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{x} \]

18384

\[ {}y^{\prime \prime }-y = {\mathrm e}^{-x} \]

18385

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 6 \,{\mathrm e}^{5 x} \]

18386

\[ {}y^{\prime \prime }-y^{\prime }+y = x^{3}-3 x^{2}+1 \]

18387

\[ {}y^{\prime \prime \prime }-2 y^{\prime }+y = 2 x^{3}-3 x^{2}+4 x +5 \]

18388

\[ {}4 y^{\prime \prime }+y = x^{4} \]

18389

\[ {}y^{\left (5\right )}-y^{\prime \prime \prime } = x^{2} \]

18390

\[ {}y^{\left (6\right )}-y = x^{10} \]